Rapid Cycling Genomic Selection in a Multiparental Tropical Maize Population. Issue 7 (1st July 2017) - Zhang, Xuecai; Pérez-Rodríguez, Paulino; Burgueño, Juan; Olsen, Michael; Buckler, Edward; Atlin, Gary; Prasanna, Boddupalli M; Vargas, Mateo; San Vicente, Félix; Crossa, José
Abstract: Genomic selection (GS) increases genetic gain by reducing the length of the selection cycle, as has been exemplified in maize using rapid cycling recombination of biparental populations. However, no results of GS applied to maize multi-parental populations have been reported so far. This study is the first to show realized genetic gains of rapid cycling genomic selection (RCGS) for four recombination cycles in a multi-parental tropical maize population. Eighteen elite tropical maize lines were intercrossed twice, and self-pollinated once, to form the cycle 0 (C0 ) training population. A total of 1000 ear-to-row C0 families was genotyped with 955, 690 genotyping-by-sequencing SNP markers; their testcrosses were phenotyped at four optimal locations in Mexico to form the training population. Individuals from families with the best plant types, maturity, and grain yield were selected and intermated to form RCGS cycle 1 (C1 ). Predictions of the genotyped individuals forming cycle C1 were made, and the best predicted grain yielders were selected as parents of C2 ; this was repeated for more cycles (C2, C3, and C4 ), thereby achieving two cycles per year. Multi-environment trials of individuals from populations C0, C1, C2, C3, and C4, together with four benchmark checks were evaluated at two locations in Mexico. Results indicated that realized grain yield from C1 to C4 reached 0.225 ton ha −1 per cycle, which is equivalent to 0.100 ton ha −1  yr −1 over a 4.5-yr breeding period from the initial cross to the last cycle. Compared with the original 18 parents used to form cycle 0 (C0 ), genetic diversity narrowed only slightly during the last GS cycles (C3 and C4 ). Results indicate that, in tropical maize multi-parental breeding populations, RCGS can be an effective breeding strategy for simultaneously conserving genetic diversity and achieving high genetic gains in a short period of time.